Behaviour of cold-formed steel-concrete composite columns under axial compression: Experimental and numerical study. (October 2022) - R., Senthilkumar; M., Divya; S., Divya Roy; A., Bahurudeen; Avudaiappan, Siva; Tsavdaridis, Konstantinos Daniel
Abstract: Concrete filled cold-formed steel-concrete composite columns exhibit improved strength and ductility characteristics due to its ability to resist inward buckling as well as delay the outward buckling. Though concrete infill prevents inward buckling, outward buckling still limits the steel section from reaching its yield strength. From the past studies, it is observed that the introducing of web stiffeners in cross-section of steel section may improve its buckling resistance. The present study focuses on assessing the effect of longitudinal stiffeners on the behaviour of square cold-formed steel–concrete composite columns for the various slenderness range (0.01 to 0.4) through experimental and numerical studies. Conventionally, the integrity of hollow tube cross sections is ensured by welding or by rolling process during the manufacturing. Welding process cannot be adopted in thin-walled cold formed sections since it may lead to higher degree of imperfection. In this study, the desired square cross sections were formed from flat steel sheet and overlapped using self-tapping screws. An intensive numerical analysis was carried out by varying stiffener angle as 90°, 120°, and 141° and the buckling curves for plain and profiled sections were presented. It is concluded that the axial compressive strength of plain and stiffened composite sections is almost equal, attributed to the inability of concrete to reach its maximum stress due to stress concentration at the stiffeners' edges. The buckling reduction factor of stiffened composite columns showed higher values in the higher slenderness range, indicating the positive effect of the stiffeners.